Vascular hyperpolarization in human physiology and cardiovascular risk conditions and disease - Schinzari, F.; Tesauro, M.; Cardillo, C. (Acta Physiologica, 2017)
Hyperpolarization causing smooth muscle relaxation contributes to the maintenance of vascular homeostasis, particularly in small‐calibre arteries and arterioles. It may also become a compensatory vasodilator mechanism upregulated in states with impaired nitric oxide (NO) availability. Bioassay of vascular hyperpolarization in the human circulation has been hampered by the complexity of mechanisms involved and the limited availability of investigational tools. Firm evidence, however, supports the notion that hyperpolarization participates in the regulation of resting vasodilator tone and vascular reactivity in healthy subjects. In addition, an enhanced endothelium‐derived hyperpolarization contributes to both resting and agonist‐stimulated vasodilation in a variety of cardiovascular risk conditions and disease. Thus, hyperpolarization mediated by epoxyeicosatrienoic acids (EETs) and H2O2 has been observed in coronary arterioles of patients with coronary artery disease. Similarly, ouabain‐sensitive and EETs‐mediated hyperpolarization has been observed to compensate for NO deficiency in patients with essential hypertension. Moreover, in non‐hypertensive patients with multiple cardiovascular risk factors and in hypercholesterolaemia, KCa channel‐mediated vasodilation appears to be activated. A novel paradigm establishes that perivascular adipose tissue (PVAT) is an additional regulator of vascular tone/function and endothelium is not the only agent in vascular hyperpolarization. Indeed, some PVAT‐derived relaxing substances, such as adiponectin and angiotensin 1‐7, may exert anticontractile and vasodilator actions by the opening of KCa channels in smooth muscle cells. Conversely, PVAT‐derived factors impair coronary vasodilation via differential inhibition of some K+ channels. In view of adipose tissue abnormalities occurring in human obesity, changes in PVAT‐dependent hyperpolarization may be relevant for vascular dysfunction also in this condition.